Hygienic design of food factories. - Holah, J. T.; Lelieveld, H. L. M.; Moerman, Frank (Woodhead Publishing, an imprint of Elsevier, 2023)
"Advances in food safety knowledge, combined with the continuing rapid development of new food products, have had an impact on the need for improved hygiene in the food manufacturing infrastructure. This has created a need for the second edition of Hygienic Design of Food Factories, which expands all existing chapters and includes new topics, such as cold storage and the control of air in food refrigeration facilities. Additionally, chapters explore the prevention of food contamination when building during production, the risk assessment of which is becoming important globally, and hygienic building design regulations in Russia and Brazil. Divided into 6 parts, the book is now thoroughly updated and expanded. Part one reviews the implications of hygiene and construction regulation in various countries on food factory design, while taking into account retailer requirements as well. Part two describes site selection, factory layout and the associated issue of airflow. Parts three through four and five then address the hygienic design of the essential parts of a food factory. These include walls, ceilings, floors, selected utility and process support systems, entry and exit points, storage areas and changing rooms. Lastly part six covers the management of building work and factory inspection when commissioning the plant. With its distinguished editors and international team of contributors, Hygienic Design of Food Factories, 2nd edition, continues to be an essential reference for managers of food factories, food plant engineers and all those with an academic research interest in the field." -- Provided by publisher.
Keywords: Food processing plants -- Design and construction.; Food processing plants -- Design -- Handbooks, manuals, etc.; Manufacturing processes -- Design -- Handbooks, manuals, etc.; elektronické knihy; electronic books